Chronic pain comorbid with mental disorders: literature review and clinical case - Dmitry S. Petelin; Maya V. Ksenofontova; Polina S. Isaeva; Olga Yu. Sorokina; Beatrice A. Volel (LLC "MEDIAFORMAT", 2024)
Chronic pain is one of the main problems of modern clinical medicine. It is associated with its high prevalence, negative impact on the level of development and the life quality of patients, as well as difficulties in selecting effective drug therapy. According to various data, the population prevalence of chronic pain during life varies from 11% to 40%. Modern publications have proven the connection of various pain syndromes with unpredictable psychopathological conditions, including affective disorders, anxiety disorders, addiction to psychoactive substances, and personality disorders. Currently, a large number of methods that reduce the severity of chronic pain are available. Due to the emphasis of this article on the consequences associated with painful disorders, only methods used in psychiatric practice are discussed. This includes psychopharmacotherapy, psychotherapy and non-drug biological methods of therapy. In order to illustrate the main provisions presented in the review literature, the article offers a clinical observation.